Strep-tag II fusion technology for the modification and immobilization of lipase B from Candida antarctica (CALB) - Sumreet Singh Johar; Joey N. Talbert (Journal of Genetic Engineering and Biotechnology, 2017)
Fusion tags – amino acid sequences that are genetically coded to be expressed as attached moieties to a protein – have the potential to enhance the activity of native enzyme, enable specific purification of the enzyme, and promote simple and efficient immobilization of enzymes onto material supports. In this work, we demonstrate the effect of a Strep-tag II fusion tag on the properties of free and immobilized lipase B from Candida antarctica (CALB). The gene encoding the mature portion of CALB was codon-optimized and cloned in pASG-IBA2 plasmid for expression in E. coli. Purified recombinant Strep-tag II CALB was immobilized to Strep-Tactin based support through affinity binding, and the immobilized and free Strep-tag II CALB were compared to a commercial CALB. Following modification, the enzyme could be selectively purified from culture media with no observable non-specific binding. The catalytic efficiency of the purified fusion-tagged enzyme was significantly greater than that of the commercial CALB in its free form. Immobilization of the fusion-tagged enzyme to Strep-Tactin modified crosslinked agarose support yielded a catalytically active enzyme; however, the kcat of the immobilized enzyme was significantly reduced compared to the free tagged enzyme. This work indicates that a C-terminus Strep-tag II fusion tag may be employed to improve the catalytic efficiency of free CALB, but may not be suitable for immobilized applications that employ binding of the enzyme to a Strep-Tactin-modified support.